Excès et sacré dans la littérature victorienne et édouardienne - Annie Escuret (Cahiers Victoriens et Edouardiens)
During the 20th century there was an explosion of literary forms like the magic realism of Salman Rushdie who dared to rewrite texts considered as « sacred » by some who tried to punish him for his transgressions but what about the 19th century ? How did the most eminent Victorian writers manage to negotiate with the various representations of the « other » ? Dickens seems to tower above his contemporaries with his unusual production and by creating excessive characters (like Miss Havisham). Unlike Lewis Carroll and Edward Lear who practised the art of controlled transgression, Hardy stands out as « Hardy the Degenerate » because he was bold enough to resort to blasphemy in his last novel Jude the Obscure. Trollope looks like a stable island but why such a massive production (as if he was trying to dam some gap) ? What strikes us with Meredith is his (excessive ?) sophistication, an expert in the literary deconstruction of the Bible’s master stories. Even George Eliot creates characters that symbolize excess or chaos. Unlike her sisters, Emily Brontë stands, in her solitude, for some form of sacred violence and for the rejection of the identification of God with reason. This means that we are confronted with two sorts of Victorian writers : those who assimilate and swallow as opposed to those who « vomit ». Some writers (like Dickens or Virginia Woolf) do insist on the importance of immanent forms of the sacred whereas Hardy and Conrad insist mainly on the absence of any form of sacredness. Bataille constructs his heterology around the threshold of the sacred, the line marked by interdictions that solicit transgressive action. If heterology centers on the sacred as posited by those things which are hidden, objects of revulsion such as the body’s excreta (tears, sweat, blood…), the sacrificial banquet stands for the opposite, for ingestion and communion.